2012
DOI: 10.12968/bjcn.2012.17.10.474
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous therapy: guidance on devices, management and care

Abstract: This article aims to provide guidance for practitioners on intravenous therapy devices, their management and care. It explains the indications for their use and considerations when selecting devices for intravenous therapy and treatment. Both PVADs and CVADs are discussed in detail to provide the practitioner with a clear understanding for each. Infection control and how to reduce infection risks are also addressed with recommendations for best practice guidance on flushing devices, minimising complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…37,38 In addition, low adherence to hand hygiene has been associated with high rates of CRBSI, also highlighting the importance of adequate team training. 39,40 Some studies also investigated the microbial composition of the biofilms in CVCs, revealing a predominant presence of gram-positive microorganisms, such as Staphylococcus aureus and coagulase-negative staphylococci (bacteria) and Candida albicans (yeast), especially in immunocompromised patients with prolonged catheterization. 9 It is important to highlight that Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 In addition, low adherence to hand hygiene has been associated with high rates of CRBSI, also highlighting the importance of adequate team training. 39,40 Some studies also investigated the microbial composition of the biofilms in CVCs, revealing a predominant presence of gram-positive microorganisms, such as Staphylococcus aureus and coagulase-negative staphylococci (bacteria) and Candida albicans (yeast), especially in immunocompromised patients with prolonged catheterization. 9 It is important to highlight that Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…Outro fator a ser considerado é o tempo de espera da secagem do antisséptico antes da realização da punção. 5,10,[16][17][18][19][20][29][30][31][32][33] Técnica estéril e antissepsia da pele são consideradas intervenções importantes na prevenção de infecção. Estudos recentes demonstram que a clorexidina deve ser preferencialmente utilizada, pois a incidência de infecção é 50% menor quando comparada ao PVP-I (Iodopovidona ou Povidona-iodo), devido à maior ação residual, prevenindo a recolonização da pele.…”
Section: Discussionunclassified
“…Therefore, there is a need for knowledge, skills and training for the safe management of intravascular devices. 5 It is reported that the occurrence of adverse events (AE) has a significant impact on the Unified Health System (UHS), resulting in an increase in morbidity and mortality, in the time of treatment of patients and in care costs, as well as repercussions in other fields of social life and economic. 6 It is recalled that patient safety can be defined as preventing, preventing or improving adverse outcomes or injuries arising from the medical-hospital and home care process.…”
Section: Original Articlementioning
confidence: 99%
“…São José do Rio Preto (SP), Brazil. E-mail: isabelashumaher@gmail.com ORCID iD: http://orcid.org/0000-0001-8852-0294; 5 PhD student, Medical School of São José do Rio Preto / FAMERP. São José do Rio Preto (SP), Brazil.…”
Section: Introductionmentioning
confidence: 99%